EMPOWERING STUDENTS THROUGH THE IMPLEMENTATION OF PORTFOLIO ASSESSMENT - Ekawati, Dian (2006)
The study entitled "Empowering Students through the Implementation of Portfolio Assessment (A Case Study of Second-Grade Students of SMUN 8 Bandung) attempts to investigate the accomplishment of portfolio in classroom use, which is considered to empower the students in their learning process. Started from the assumption that standardized test will not provide such empowerment, this research was conducted. The research questions were proposed in order to guide the research focusing on the problem. The questions are (1) How portfolio assessment is carried out in classroom setting and (2) How portfolios can empower the students socially, cognitively, and psychologically in their learning process.The present study is qualitative in nature with single research site that is a classroom in SMUN 8 Bandung. By spreading questionnaires, doing interviews, and having observations on 31 respondents-1 teacher and 30 students, the data were collected and analyzed. Emic perspectives were used here as the primary data source.In order to have better insight to the research problem, triangulation method was used in this research.The investigation found that specific steps were accomplished to make portfolio assessment possible to implement for reaching optimal assessment. Moreover, the data shows that portfolio assessment can truly empower the students in three domains: social, cognitive and psychological factors. These empowerments are remarkably derived from students' effort as they are engaged in portfolio assessment.The research finally comes to the conclusion that the portfolio assessment will reach its goal if it is carried out effectively. All in all, the effective implementation will route the students to gain empowerment socially, cognitively, and psychologically. It also suggests all participants who involved in the assessment should take initiatives to take a part in the assessment.Hopefully, the findings will be useful to inform other teaching practitioners, who want to conduct the assessment and to give portrays of portfolio implementation.It is also recommended that portfolio assessment can be implemented in schools in order to have the enhancement of English teaching and learning process especially in assessment system.